Soil spectral characteristics and their predictive value in relation to spatial and temporal variability in wheat yield and soil quality within a long-term field trial - Ngejane, Nompumelelo (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.